Cost-Effectiveness of Alternating MRI and Digital Mammography Screening in BRCA1 and BRCA2 Gene Mutation Carriers - Cott Chubiz, Jessica E (2012)
BACKGROUND: Current clinical guidelines recommend earlier, more intensive breast cancer screening with both MRI and mammography for women with BRCA mutations. Unspecified details of screening schedules are a challenge for implementing guidelines. METHODS: A Markov Monte Carlo computer model simulated screening in asymptomatic female BRCA1 and BRCA2 mutation carriers. Three dual-modality strategies were compared with digital mammography (DM) alone: 1) DM and MRI alternating at 6-month intervals beginning at age 25 [Alt25], 2) annual MRI beginning at age 25 with alternating DM added at age 30 [MRI25/Alt30], and 3) DM and MRI alternating at 6-month intervals beginning at age 30 [Alt30]. Primary outcomes were quality-adjusted life years (QALYs), lifetime costs (in 2010 USD), and incremental cost-effectiveness ($/QALY gained). Additional outcomes included potential harms of screening, and lifetime costs stratified into component categories (screening and diagnosis, treatment, mortality, and patient time costs). RESULTS: All three dual-modality screening strategies increased QALYs and costs. Alt30 screening had the lowest incremental costs per additional QALY gained: (BRCA1: $74,200/QALY; BRCA2: $215,700/QALY). False-positive test results increased substantially with dual-modality screening, occurring more frequently in BRCA2 carriers. Downstream savings in both breast cancer treatment and mortality costs were outweighed by increases in up-front screening and diagnosis costs. Results were most influenced by estimates of breast cancer risk and MRI cost. CONCLUSIONS: Alternating MRI and DM screening at 6-month intervals beginning at age 30 is a clinically effective approach to applying current guidelines, and is more cost-effective in BRCA1 compared with BRCA2 gene mutation carriers.